The Effect of Tax Ethics and Tax Morals on Tax Evasion - Cherly Elisabeth (Golden Ratio of Taxation Studies, 2022)
This study aims to determine the effect of tax justice, tax system, tax discrimination, tax understanding and tax compliance on tax evasion. The population in this study were individual taxpayers registered at the North Makassar Primary Tax Service Office. The sampling technique used purposive sampling method. Respondents of this study were 100 respondents. Data collection using questionnaire method. The analysis method uses multiple linear regression with the help of the SPSS version 25 program. The results showed that tax justice has a significant negative effect on tax evasion, the tax system has no negative effect on tax evasion, tax discrimination has a significant positive effect on tax evasion, tax understanding has a significant negative effect on tax evasion and tax compliance has a significant negative effect on tax evasion.